2009
DOI: 10.1051/0004-6361/200911662
|View full text |Cite
|
Sign up to set email alerts
|

Early-type stars in the young open cluster NGC 2244 and in the Monoceros OB2 association

Abstract: Aims. We present the results obtained from a long-term spectroscopic campaign to study the multiplicity of O-type stars in both the young open cluster NGC 2244 and the Mon OB2 association. Methods. Our spectroscopic monitoring was performed over several years, allowing us to investigate different timescales. For each star, several spectral diagnostic tools were applied to search for line shifts and profile variations. We also measured the projected rotational velocity and revisited the spectral classification.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
94
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 58 publications
(104 citation statements)
references
References 55 publications
(154 reference statements)
8
94
2
Order By: Relevance
“…With only five binaries or binary candidates (including WR 20a and the three eclipsing OB systems, two of which host B-type primaries) out of the fifteen stars investigated, our results are more reminiscent of the situation encountered in IC 1805 (De Becker et al 2006;Hillwig et al 2006) and NGC 2244 (Mahy et al 2009). If we restrict ourselves to O-type stars, the fraction of confirmed or candidate binaries drops to about 15% (2 out of 13).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…With only five binaries or binary candidates (including WR 20a and the three eclipsing OB systems, two of which host B-type primaries) out of the fifteen stars investigated, our results are more reminiscent of the situation encountered in IC 1805 (De Becker et al 2006;Hillwig et al 2006) and NGC 2244 (Mahy et al 2009). If we restrict ourselves to O-type stars, the fraction of confirmed or candidate binaries drops to about 15% (2 out of 13).…”
Section: Discussionmentioning
confidence: 69%
“…If we restrict ourselves to O-type stars, the fraction of confirmed or candidate binaries drops to about 15% (2 out of 13). Given the higher stellar density in the core of NGC 6231 than in both NGC 2244 and IC 1805, Mahy et al (2009) tentatively suggested that the number of short-period early-type binary systems might be correlated with the cluster density. However, with its rather large cluster density and low fraction of short-period massive binaries, Westerlund 2 apparently does not follow such a correlation.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the tentative variability observed in the giant sample is also unclear: binarity or wind or photospheric variability? Of the five dwarfs or subgiants, HD 48279 is constant in radial velocity (Mahy et al 2009), HD 12323 is a single-lined spectroscopic binary (SB1; Bolton & Rogers 1978), HD 14633 an SB1 with a low-mass component and high eccentricity (Boyajian et al 2005), HD 102415 is reported as "likely variable" by Walborn et al (2011), and HD 201345 has an unclear status. Figure 11 provides more information on the line-profile and radial-velocity variations of ten of the ON stars studied in the present paper.…”
Section: Rotation and The On Phenomenonmentioning
confidence: 99%
“…In addition to shaping the surface of the star and modifying the surface temperature (poles being hotter than the equator), it triggers internal mixing processes A&A 538, A39 (2012) Notes. Spectral types are from Sota et al (2011) and Mahy et al (2009). Magnitudes are from Maíz-Apellániz et al (2004).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, this region contains a homogeneous sample of O stars with different masses and luminosities, but most likely the same age. Binaries are also present (Mahy et al 2009). As such, this sample is well suited to investigating the effects of rotation on massive stars surface abundances.…”
Section: Introductionmentioning
confidence: 99%